KONTRIBUSI FLEKSIBILITAS DAN POWER LENGAN KEPADA JUMP SPIN SERVIS BOLAVOLI - Ma'mun, Sukron (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
Flexibility and arm power have a strategic contribution in finishing matches in the sport of volleyball, by having good flexibility and arm power the results of the service will be accurate. This research uses quantitative methods where the results of this research are in the form of data and numbers. The sample in this study consisted of 18 volleyball athletes. The instruments in this study used the sit and reach to test flexibility, the medicine ball throw to test arm power, and the jump spin serve test to determine volleyball serve results. The results of this research show that the contribution of body flexibility and arm power has a significant influence on the accuracy of the jump serve technique in volleyball, which can produce an influence of 62.7% for jump spin serves and 69.5% for jump float serves. It is hoped that the results of this research will be a guide for coaches and volleyball coaches. As a result, future researchers can further develop the results of this research.